Challenges of Federalism in Nepal: Exploring Strategies for Effective Implementation (Pragya Darshan प्रज्ञा दर्शन, 2025)
"Challenges of Federalism in Nepal: Exploring Strategies for Effective Implementation", the research topic has been selected by the researcher in the interest of gaining knowledge and sharing it with other readers in order to searching its impacts by discussing, its issues in implementing and finding logical sources to make it durable in Nepal comparing with international federal democracy. This research aims to explore the challenges of implementing federalism in Nepal, focusing on its impacts, issues, and strategies for sustainable development. The study examines the concept of federalism and its relevance to Nepal, analyzing the federalization process, its historical context, and the prevailing issues in implementation. By reviewing literature, national and international sources, and secondary data, the researcher seeks to understand whether Nepal's federal democracy is functioning effectively or requires further improvement. The research identifies key challenges, including gaps between constitutional provisions and Nepal’s social structure, leadership, and political dynamics. It highlights the need for a streamlined two-tier government system, as opposed to the existing three-tier system, to enhance economic efficiency and governance. The study concludes that while federalism is essential for empowering Nepali citizens and improving resource accessibility, overcoming socio-cultural and political conflicts, bridging gaps between constitutional ideals and reality, and strengthening federal units are critical for effective implementation. The research emphasizes the importance of minimizing social, cultural, and ethnic conflicts, promoting adherence to constitutional provisions, and empowering federal institutions to ensure the success of federalism in Nepal.